2023
DOI: 10.1371/journal.pmed.1004309
|View full text |Cite
|
Sign up to set email alerts
|

Patents and regulatory exclusivities on FDA-approved insulin products: A longitudinal database study, 1986–2019

Anders Olsen,
Reed F. Beall,
Ryan P. Knox
et al.

Abstract: Background Insulin is the primary treatment for type 1 and some type 2 diabetes but remains costly in the United States, even though it was discovered more than a century ago. High prices can lead to nonadherence and are often sustained by patents and regulatory exclusivities that limit competition on brand-name products. We sought to examine how manufacturers have used patents and regulatory exclusivities on insulin products approved from 1986 to 2019 to extend periods of market exclusivity. Methods and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Such reliance on disconnected device patents goes beyond what has been observed for other drug-device combinations: 23% of distinct FDA-listed device patents on inhalers and 15% on insulin pens mention the products’ active ingredients in their claims compared with no such mentions among device patents on GLP-1 receptor agonists.…”
Section: Discussionmentioning
confidence: 98%
“…Such reliance on disconnected device patents goes beyond what has been observed for other drug-device combinations: 23% of distinct FDA-listed device patents on inhalers and 15% on insulin pens mention the products’ active ingredients in their claims compared with no such mentions among device patents on GLP-1 receptor agonists.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study of insulin products found that the last-to-expire patents on almost a third of the products studied did not mention the active ingredient (insulin) at all. Yet, these patents extended the market monopoly of the corresponding insulin products by a median of 4.3 years, delaying biosimilar entries and protecting the brand products’ monopoly pricing [ 25 ].…”
mentioning
confidence: 99%